2021
DOI: 10.3389/fphar.2021.648668
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Approach to Optimizing Dose Regimen of Vancomycin for Chinese Pediatric Patients with Gram-Positive Bacterial Infections

Abstract: The aim of this study was to establish the population pharmacokinetics (PK) model of Vancomycin for Chinese pediatric patients which can extrapolate to whole age periods by bridging the published adult population PK model and the established pediatric population PK model. The final consolidated population PK model was used to explore the correlation of pharmacokinetics/pharmacodynamics (PK/PD) indices and efficacy of vancomycin and to provide evidence for the optimized regimen of vancomycin in Chinese pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…According to the latest international guidelines, monitoring the AUC 24 /MIC for vancomycin is recommended, with a target range of 400-600 [2] . Nevertheless, the practicality of monitoring AUC 24 /MIC in clinical settings is limited due to various factors, including the necessity for secondary sampling, the scarcity of specialized personnel, and the ambiguity surrounding PK/PD standards for pediatric patients [23] . Consequently, monitoring C min remains a widely adopted practice, even in most large tertiary medical institutions, emphasizing the crucial importance of further exploring the rational use of vancomycin through C min monitoring [24] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest international guidelines, monitoring the AUC 24 /MIC for vancomycin is recommended, with a target range of 400-600 [2] . Nevertheless, the practicality of monitoring AUC 24 /MIC in clinical settings is limited due to various factors, including the necessity for secondary sampling, the scarcity of specialized personnel, and the ambiguity surrounding PK/PD standards for pediatric patients [23] . Consequently, monitoring C min remains a widely adopted practice, even in most large tertiary medical institutions, emphasizing the crucial importance of further exploring the rational use of vancomycin through C min monitoring [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff point (Figure S4) in predicting effectiveness showed that the median value of AUC/MIC was between 200 and 300 with an overall clinical effective rate of 92.6%, indicating that a relatively low exposure is effective for pediatric patients. 40 Another research in children with MRSA bacteremia showed that the relationship between vancomycin AUC 0-24 /MIC <400 and treatment failure could not be established. 41 Additionally, targeting the value above 400 in pediatrics would expose them to unnecessary adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to mention that recent research indicates a possibly lower AUC target for Chinese paediatric patients. 40 Clinicians might consider this when interpreting our model’s simulation results, and adjust the dosing regimen according to their specific clinical requirements.…”
Section: Discussionmentioning
confidence: 99%